2017
DOI: 10.1002/jcb.25906
|View full text |Cite
|
Sign up to set email alerts
|

[10]-Gingerol Reverts Malignant Phenotype of Breast Cancer Cells in 3D Culture

Abstract: Breast cancer is a complex and multifactorial disease. Tumors have a heterogeneous microenvironment, which have multiple interactions with other cell types, greatly influencing the behavior of tumor cells and response to therapy. The 3D culture mimics the microenvironment better found in vivo and is more appropriated than the traditional 2D culture made from plastic to test the cellular response to drugs. To investigate the effects of [10]-gingerol on breast tumor cells, we used physiologically relevant three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Most important is the diversity within the tumor microenvironment (TM) in terms of the stromal cells present, the amount of oxygen available and the acidity of the environment [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Another important difference is the amount of the extracellular matrix (ECM) proteins around the cancer cells [ 25 , 26 , 27 ]. ECM proteins can create a barrier through which the drugs must pass in order to reach the cancer cells while their presence promote tumor metastasis [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most important is the diversity within the tumor microenvironment (TM) in terms of the stromal cells present, the amount of oxygen available and the acidity of the environment [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Another important difference is the amount of the extracellular matrix (ECM) proteins around the cancer cells [ 25 , 26 , 27 ]. ECM proteins can create a barrier through which the drugs must pass in order to reach the cancer cells while their presence promote tumor metastasis [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that [10]-gingerol is a more potent inhibitor than [6]- or [8]-gingerol, with selectivity towards breast cancer cells compared to normal fibroblasts in vitro . In addition, more recently we have demonstrated that [10]-gingerol is able to revert the malignant phenotype of breast cancer cells in three-dimensional culture [ 20 ]. Interestingly, [10]-gingerol also mediates potent anti-neuroinflammatory activity [ 21 ], an important manifestation likely to contribute to the development of brain metastases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…10-gingerol has been previously reported to exert anti-tumor activity in TNBC, by inhibiting tumor cells proliferation, invasion, and metastasis, as well as by inducing apoptosis, both in vitro and in vivo 20,28,29 . Additionally, 10-gingerol demonstrated potent anti-tumor effects on non-TNBCs and other types of cancer 30,31 . To the best of our knowledge, 8-gingerol has not been previously reported to have anti-tumor activity in TNBC; thus, herein, we provide for the first-time evidence that suggests the potential use of 8-gingerol in TNBC treatment.…”
Section: Discussionmentioning
confidence: 99%